Ambivalence: Prerequisite for success in motivational interviewing with adolescents?. (27th January 2016) - Feldstein Ewing, Sarah W.; Apodaca, Timothy R.; Gaume, Jacques
Abstract: Background and Aims: The exploration and resolution of ambivalence play an essential role in motivational interviewing (MI) theory. However, most adolescent MI studies have not examined ambivalence as a contributor to behaviour change. This paper reviewed research findings on the role of ambivalence in the adolescent change process. Methods and results: We undertook a narrative review of the published empirical and theoretical literature on ambivalence and mechanisms of change in MI for adolescents and found that current MI evaluations appear not to have access to reliable and valid measures of ambivalence in adolescence or neuroimaging methods to evaluate the mechanisms of treatment response. Conclusions: Improved instrumentation is needed to assess adolescents' ambivalence in clinical and research settings. Innovative methodology, including neuroimaging, may help identify factors mediating relationships between adolescents' ambivalence and treatment response.